Behavioral effects of acute systemic low-dose clozapine in wild-type rats: Implications for the use of DREADDs in behavioral neuroscience - Ilg, Ann-Kathrin; Enkel, Thomas; Bartsch, Dusan; Bähner, Florian (Frontiers in behavioral neuroscience, 2018)
DREADDs (Designer Receptors Exclusively Activated by Designer Drugs) are popular tools used to manipulate the activity of defined groups of neurons. Recent work has shown that DREADD effects in the brain are most likely not mediated by the proposed ligand clozapine-N-oxide but its metabolite clozapine. However, it is not known whether low doses of clozapine required to activate DREADDs already have DREADD-independent effects on behavior as described for higher clozapine doses used in previous preclinical studies. To close this gap, we compared effects of acute systemic (i.p.) clozapine treatment vs. vehicle in a wide range of behavioral tests in male wild-type rats. We found that clozapine doses as low as 0.05-0.1 mg/kg significantly affected locomotion, anxiety and cognitive flexibility but had no effect on working memory or social interaction. These results highlight the need for careful controls in future chemogenetic experiments and show that previous results in studies lacking clozapine-N-oxide/clozapine controls may require critical re-evaluation.
Gesehen am 16.04.2020